Magnesium oxide for annealing separator and method for producing grain-oriented electrical steel sheet using the same
By using magnesium oxide with mesh and plate-like particles in the annealing separator and controlling the copper content and particle size distribution, the problem of copper diffusion affecting the magnetic characteristics of the steel plate is solved, and the effect of uniform coating and improving magnetic characteristics is achieved.
Patent Information
- Application Number
- CN202410642617.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2024-04-19
- Filing Date
- 2024-05-23
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-05-23
AI Technical Summary
The existing annealing separator contains a large amount of copper, which causes copper to diffuse to the steel plate during the high-temperature annealing process, affecting the magnetic characteristics of the steel plate.
An annealing separator mainly composed of magnesium oxide, which contains network particles and plate particles with multiple depressions on the surface. The copper content is controlled between 3 and 200 ppm. By adjusting the particle size distribution and the content of trace elements, suitable formation is formed. The viscosity of the slurry ensures uniform coating.
A uniform coating of annealing separator is achieved, forming a forsterite film with good coating characteristics, and improving the magnetic characteristics of the oriented electromagnetic steel plate.
Smart Images

Figure CN118516517B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to magnesium oxide for annealing separator (magnesium oxide for annealing separator) and a method for producing a grain-oriented electrical steel sheet using the same. Background Art
[0002] It is known that there is a method for manufacturing a grain-oriented electrical steel sheet by subjecting steel slag or molten steel to a hot rolling process, a pre-annealing process, a cold rolling process, a decarburization annealing process, and a high-temperature annealing process. During the high-temperature annealing process, an annealing separator mainly composed of magnesium oxide is applied to the surface of the steel sheet after decarburization annealing. As a result, a forsterite film is formed on the surface of the steel sheet. The coating properties of the forsterite film affect the magnetic properties of the steel sheet. Therefore, the coating properties of the forsterite film are improved. For example, Patent Document 1 discloses a magnesium oxide-based annealing separator for forming a forsterite film in the final high-temperature annealing process of a grain-oriented silicon steel sheet. The annealing separator is mainly composed of magnesium oxide. The magnesium oxide is obtained by adding Cu or a Cu compound to magnesium hydroxide in a range of 0.1 to 10 weight % in terms of metal element relative to the calcined MgO, and calcining the mixture. According to Patent Document 1, by introducing Cu into the annealing separator, the coating properties of the forsterite coating, namely, the uniformity of the appearance, the adhesion and the occupancy rate can be improved.
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: Japanese Patent Application Laid-Open No. 4-56781 Summary of the invention
[0006] Problems to be solved by the invention
[0007] According to Patent Document 1, it is believed that if copper (Cu) is contained in the annealing separator in the range of 0.1 to 10 weight %, the coating properties of the forsterite coating are improved. However, since the annealing separator contains a large amount of copper, a large amount of copper may diffuse into the steel sheet during the high temperature annealing process. In this case, the copper content in the steel sheet is too high, which may have an adverse effect on the magnetic properties of the steel sheet.
[0008] In order to obtain a forsterite coating having good coating properties without being affected by the amount of copper, it is important to uniformly apply the slurry of the annealing separator on the steel sheet.
[0009] An object of the present invention is to provide magnesium oxide for an annealing separator capable of uniformly applying a slurry of magnesium oxide for an annealing separator to a steel sheet, and a method for producing a grain-oriented electrical steel sheet using the same.
[0010] Means of solving problems
[0011] The present invention includes the following disclosures.
[0012] (First Publication)
[0013] The first disclosure is magnesium oxide for annealing separators mainly composed of magnesium oxide. The magnesium oxide for annealing separators comprises mesh particles having a plurality of depressions on the surface and plate particles, wherein the ratio of the number of the plate particles to the number of the mesh particles is 1:99 to 20:80.
[0014] (Second Publication)
[0015] The second disclosure is the invention according to the first disclosure, wherein in the mesh particle, the particle size of the mesh particle is 0.05 to 5 μm, and the size of each of the plurality of depressions of the mesh particle is 0.005 to 0.2 μm.
[0016] (3rd Publication)
[0017] The third disclosure is that in the first disclosure or the second disclosure, the plate-like particles have a particle size of 0.05 to 5 μm.
[0018] (4th Publication)
[0019] The fourth disclosure is any one of the first to third disclosures, wherein the magnesium oxide contains copper, and the content of the copper is 3 to 200 ppm.
[0020] (5th Publication)
[0021] The fifth disclosure is that in any one of the first to fourth disclosures, in the particle size distribution of the magnesium oxide, D10 is 0.65 to 1.7 μm. In the particle size distribution, D50 is 1.5 to 3.6 μm. In the particle size distribution, D90 is 2.0 to 14 μm. In the particle size distribution, the volume average diameter is 1.55 to 6.4 μm.
[0022] (6th Publication)
[0023] The sixth disclosure is any one of the first to fifth disclosures, wherein the magnesium oxide further includes agglomerated particles larger than the plate-like particles and the mesh-like particles.
[0024] (7th Publication)
[0025] The seventh disclosure is that in any one of the first to sixth disclosures, when a slurry containing 5 to 30 mass % of the magnesium oxide for annealing separator is formed using water as a solvent, the viscosity of the slurry at 5° C. is 2.2 to 5.2 mPa·s.
[0026] (8th Publication)
[0027] The eighth disclosure is a method for manufacturing a grain-oriented electrical steel sheet. The method for manufacturing a grain-oriented electrical steel sheet includes a coating step and a high-temperature annealing step. The coating step is a step of coating a slurry containing the magnesium oxide for annealing separator described in any one of the first disclosure to the seventh disclosure on a decarburization annealed steel sheet. The high-temperature annealing step is a step of annealing the steel sheet coated with the slurry.
[0028] Effects of the Invention
[0029] According to the present invention, it is possible to provide magnesium oxide for annealing separator which enables uniform application of a slurry of magnesium oxide for annealing separator on a steel sheet, and a method for producing a grain-oriented electrical steel sheet using the same. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is a schematic diagram showing an example of mesh-like particles and plate-like particles in magnesium oxide for an annealing separator according to an embodiment.
[0031] Figure 2 This is a SEM photograph showing examples of mesh-like particles and plate-like particles in magnesium oxide of Example 1.
[0032] Figure 3 This is a SEM photograph showing an example of agglomerated particles in magnesium oxide of Example 1 to which agglomerated particles are added.
[0033] Figure 4 This is a SEM photograph showing an example of particles in magnesium oxide of Comparative Example 1.
[0034] Figure 5 This is a graph showing an example of pore distribution in magnesium oxide of Example 1.
[0035] Figure 6 This is a graph showing an example of pore distribution in magnesium oxide of Example 2.
[0036] Figure 7 This is a graph showing an example of pore distribution in magnesium oxide of Example 3.
[0037] Figure 8 This is a graph showing an example of pore distribution in magnesium oxide of Comparative Example 1.
[0038] Fig. 9 This is a graph showing an example of pore distribution in magnesium oxide of Comparative Example 3.
[0039] Fig.10 This is a graph showing an example of pore distribution in magnesium oxide of Comparative Example 4.
[0040] Fig.11This is an optical observation image showing an example of the coating test result of magnesium oxide in Example 1.
[0041] Fig.12 This is a 3D observation image showing an example of the coating test result of magnesium oxide in Example 1.
[0042] Fig.13 This is a 3D observation image showing an example of the coating test result of magnesium oxide in Example 2.
[0043] Fig.14 This is a 3D observation image showing an example of the coating test result of magnesium oxide in Example 3.
[0044] Fig.15 This is an optical observation image showing an example of the coating test result of magnesium oxide in Comparative Example 1.
[0045] Fig.16 This is a 3D observation image showing an example of the coating test result of magnesium oxide in Comparative Example 1.
[0046] Fig.17 This is a 3D observation image showing an example of the coating test result of magnesium oxide in Comparative Example 3.
[0047] Fig.18 This is a 3D observation image showing an example of the coating test result of magnesium oxide in Comparative Example 4. DETAILED DESCRIPTION
[0048] Hereinafter, preferred embodiments of the magnesium oxide for annealing separator and the method for producing a grain-oriented electrical steel sheet using the magnesium oxide of the present invention will be described.
[0049] [Magnesium oxide for annealing separator]
[0050] The magnesium oxide used in the annealing separator of the present invention is a powder with magnesium oxide as the main component. Hereinafter, the magnesium oxide used in the annealing separator is also referred to as magnesium oxide. Magnesium oxide includes mesh particles and plate-like particles. Mesh particles refer to particles having multiple depressions on the surface of the magnesium oxide particles constituting magnesium oxide. In other words, mesh particles are mesh particles having a skeleton portion forming a mesh portion and a depression portion forming a mesh portion. However, the skeleton portion may also be a flat plate. Part or all of the skeleton portion may be a shape that is bent or deformed in any direction. Part or all of the depressions of the mesh particles may include through holes that penetrate the magnesium oxide particles (skeleton portion).
[0051] Figure 1 It is a schematic diagram showing an example of mesh-like particles and plate-like particles in magnesium oxide according to the embodiment. Figure 1 (a) shows a mesh particle 1 . Figure 1 (b) shows the plate-shaped particle 2.
[0052] like Figure 1 As shown in (a), the mesh particle 1 is a particle having a plurality of depressions 12 on the surface 11 of a plate-like particle. The planar shape of the mesh particle 1 is not particularly limited. Examples of the planar shape of the mesh particle 1 include: a thin plate-like polygon, a rectangle, a polygon, an ellipse, a circle, an amorphous shape, and a combination thereof. The planar shape of the depression 12 is not particularly limited. Examples of the planar shape of the depression 12 include: a polygon, a rectangle, a polygon, an ellipse, a circle, an amorphous shape, and a combination thereof. The configuration of the depression 12 on the surface 11 of the mesh particle 1 is not particularly limited. Examples of the configuration of the depression 12 include: a staggered shape, a matrix shape, a random shape, and a combination thereof. It should be noted that, in addition to being a thin plate-like polygon, the skeleton portion of the mesh particle is Figure 1 In addition to the flat plate shape shown in (a), although not shown in the figure, the shape may be bent or deformed in any direction.
[0053] like Figure 1 As shown in (b), the plate-like particle 2 is a particle without obvious depressions on the surface 21 of the plate-like particle. In other words, the plate-like particle 2 is a particle with a flat surface 21. However, although it is not the degree of the depression 12 seen in the above-mentioned mesh particle 1, it can also have a small amount of shallow depressions. The planar shape of the plate-like particle 2 is not particularly limited. Examples of the planar shape of the plate-like particle 2 include: thin plate-like polygons, rectangles, polygons, ellipses, circles, amorphous shapes, and combinations thereof.
[0054] In magnesium oxide, magnesium oxide particles as the main component contain mesh particles and plate-like particles. Therefore, when magnesium oxide is mixed in a liquid such as water, magnesium oxide is dissolved in water mainly due to the presence of mesh particles and is not easy to condense in the liquid. Furthermore, magnesium oxide is easily dispersed in the solution separately from each other mainly due to the presence of plate-like particles. Thus, a slurry in which magnesium oxide is roughly uniformly dispersed in the liquid can be obtained. By applying the slurry on a steel plate, a coating film in which magnesium oxide is roughly uniformly dispersed can be formed on the steel plate. That is, by the magnesium oxide of this embodiment, magnesium oxide can be easily and fully dispersed in the liquid, and magnesium oxide can be applied as uniformly as possible on the steel plate.
[0055] The particle size of the mesh particles is not particularly limited as long as it is a size that can form a depression. As the particle size of the mesh particles, for example, 0.05 to 5 μm can be cited. From the viewpoint of making it difficult for the particles to agglomerate in the slurry, the lower limit of the particle size of the mesh particles is preferably 0.1 μm. From the viewpoint of making the particles uniformly dispersed in the slurry, the upper limit of the particle size of the mesh particles is preferably 4 μm. As described later, the particle size of the mesh particles can be measured using a 20,000-fold scanning electron microscope (SEM) photograph.
[0056] The pore size of the depression of the mesh particle is not particularly limited as long as it has a depressed shape. As the pore size of the depression, for example, 0.005 to 0.2 μm can be cited. From the viewpoint that the particles are easy to retain moisture in the slurry, the lower limit of the pore size of the depression is preferably 0.01 μm. From the viewpoint of the size of multiple depressions that can be formed in the particles, the upper limit of the pore size of the depression is preferably 0.15 μm. As described later, the pore size of the depression can be measured using a 20,000-fold scanning electron microscope (SEM) photograph.
[0057] The particle size of the plate-like particles is not particularly limited as long as it is the same size as the mesh particles. As the particle size of the plate-like particles, for example, 0.05 to 5 μm can be cited. From the viewpoint of stably dispersing the particles in the slurry, the lower limit of the particle size of the plate-like particles is preferably 0.1 μm. From the viewpoint of uniformly dispersing the particles in the slurry, the upper limit of the particle size of the plate-like particles is preferably 4 μm. As described later, the particle size of the plate-like particles can be measured using a 20,000-fold scanning electron microscope (SEM) photograph.
[0058] However, magnesium oxide is not necessarily composed entirely of mesh particles and plate-like particles. The total ratio of mesh particles and plate-like particles relative to the overall magnesium oxide is preferably 70% by weight or more. Consider from the viewpoint of the effect of magnesium oxide having mesh particles and plate-like particles. The ratio is more preferably 90% by weight or more. The ratio is further preferably 95% by weight or more. As described later, the ratio can be determined, for example, by a scanning electron microscope (SEM) photograph taken at a magnification of 20,000 times or more.
[0059] As the relationship between the number of mesh particles contained in magnesium oxide and the number of plate-like particles, the number of mesh particles is preferably more than the number of plate-like particles. By making the number of mesh particles more, the mesh particles in the slurry are easy to keep appropriate moisture and the plate-like particles are easy to contribute to the synergistic effect of the dispersibility of particles, and a coating film with higher uniformity and fewer lumps (agglomerations) can be obtained. As described later, the comparison of the number of particles can be determined, for example, by a scanning electron microscope (SEM) photo taken at a magnification of more than 20,000 times.
[0060] As the relationship between the number of mesh particles and the number of plate-like particles contained in magnesium oxide, (the number of plate-like particles): (the number of mesh particles) can be, for example, 1:99 to 20:80 (wherein the total ratio is set to 100). (The number of plate-like particles): (the number of mesh particles) is preferably 5:95 to 15:85. By making the ratio of the number of mesh particles to the number of plate-like particles in magnesium oxide within the above range, when magnesium oxide is suspended in a liquid such as water, it is easier to obtain a slurry viscosity suitable for coating. Furthermore, in magnesium oxide, maintaining an appropriate amount of moisture through mesh particles and plate-like particles contributes to the dispersibility of particles, and can ensure a coating property with higher uniformity and less lumps (agglomerations).
[0061] Alternatively, as the relationship between the mesh particles and the plate-like particles contained in the magnesium oxide, (the weight of the plate-like particles): (the weight of the mesh particles) can be, for example, 1:99 to 20:80 (wherein the total of the ratio is set to 100). (The weight of the plate-like particles): (the weight of the mesh particles) is preferably 5:95 to 15:85. By making the ratio of the number of mesh particles to the number of plate-like particles in the magnesium oxide within the above range, when the magnesium oxide is suspended in a liquid such as water, it is easier to obtain a slurry viscosity suitable for coating. Furthermore, in magnesium oxide, the mesh particles maintain an appropriate amount of moisture and the plate-like particles contribute to the dispersibility of the particles, and a coating property with higher uniformity and less lumps (agglomerations) can be ensured.
[0062] In addition to mesh particles and plate-like particles, magnesium oxide may also include block particles whose size is larger than plate-like particles and mesh particles. The shape of the block particles is not a two-dimensional shape like a plate, but a three-dimensional block, which is a shape in which the longest diameter (size) of the particle is within 4 times the shortest diameter (size). Such block particles can act as spacers to prevent burning when the decarburized annealed steel sheet is formed into a roll shape for high-temperature annealing. The block particles have multiple faces. Each of the multiple faces can be a plane, or a deformed convex or concave face. Each of the multiple faces of the block particles can be the same shape as each other, or a part or all of them can be different from each other. The block particles can also be formed by combining several block particles of different shapes. There is no special limitation on the planar shape of the block particles. As the planar shape of the block particles, for example, polygonal, rectangular, polygonal, elliptical, circular, amorphous, and a combination thereof can be cited.
[0063] The particle size of the blocky particles is not particularly limited as long as it is larger than the particle size of the plate-like particles and the mesh-like particles. As the particle size of the blocky particles, for example, a particle size greater than 5 μm and less than 100 μm can be cited. From the viewpoint of being able to act as a spacer to prevent scorching during high-temperature annealing, the lower limit of the particle size of the blocky particles is preferably 10 μm. From the viewpoint of making the particles uniformly dispersed in the slurry, the upper limit of the particle size of the blocky particles is preferably 50 μm. As described later, the particle size of the blocky particles can be measured, for example, by SEM photographs taken at a magnification of 500 times or more. The proportion of the blocky particles relative to the whole magnesium oxide can be, for example, 1 to 10 weight %. From the viewpoint of being able to act as a spacer.
[0064] The particle size distribution of magnesium oxide is not particularly limited, as long as the magnesium oxide has mesh particles and plate-like particles, preferably also blocky particles. D10 is preferably 0.65 to 1.7 μm. D50 is preferably 1.5 to 3.6 μm. D90 is preferably 2.0 to 14 μm. The volume average diameter MV can be, for example, 1.55 to 6.4 μm. In the particle size distribution of magnesium oxide, since the particle size is distributed in a relatively small but not too small range, it is possible to suppress the aggregation of particles in the slurry and improve dispersibility.
[0065] It should be noted that the main component of magnesium oxide means that the content of magnesium oxide in the annealing separator is 50% by mass or more. From the viewpoint of functioning well as an annealing separator, the content of magnesium oxide is preferably 90% by mass or more. The content of magnesium oxide is more preferably 95% by mass or more. In the present embodiment, the content of magnesium oxide in the annealing separator is 98% by mass or more.
[0066] Magnesium oxide may contain other substances besides magnesium oxide. These other substances include, for example, copper (Cu). By containing copper, the coating properties of the forsterite coating and the magnetic properties of the steel sheet can be improved. From the perspective of improving the properties, the lower limit of the content of copper relative to magnesium oxide is, for example, 3ppm, preferably 30ppm, and more preferably 50ppm. The upper limit of the content of copper relative to magnesium oxide is, for example, 200ppm, from the perspective of suppressing excessive diffusion of copper into the steel sheet.
[0067] Magnesium oxide may contain various trace elements known to help promote the formation of coatings, improve coating properties and / or improve magnetic properties of oriented electrical steel sheets. Examples of these trace elements include chlorine (Cl), boron (B), sodium (Na), phosphorus (P), aluminum (Al), titanium (Ti), manganese (Mn), calcium (Ca) and compounds thereof. For example, chlorine is an element that promotes the formation of forsterite coatings. Boron is an element that promotes the formation of forsterite coatings. Sodium is an element that regulates the formation rate of forsterite coatings. Phosphorus is an element that promotes the formation of forsterite coatings. Aluminum is an element that promotes the formation of forsterite coatings.
[0068] When water is used as a solvent to form a slurry containing 5 to 30% by mass of magnesium oxide, the viscosity of the slurry at 5°C is preferably 2.2 to 5.2 mPa·s. The more preferred lower limit is 3.5 mPa·s. By making the viscosity not too low, the coating film can be stably maintained when the slurry containing magnesium oxide is applied to the steel plate. On the other hand, by making the viscosity not too high, the slurry can be easily applied to the entire surface of the steel plate. Here, the reason for specifying the viscosity of the slurry at 5°C is as follows. When magnesium oxide is dispersed in water to form a slurry, if the slurry is formed at room temperature, the magnesium oxide is hydrated. If such a slurry containing magnesium oxide hydrate is applied to the surface of the steel plate, it is possible to have an adverse effect on the properties of the steel plate. Therefore, in order to inhibit the hydration of magnesium oxide, it is preferred to form the slurry at a low temperature such as 5°C and apply it to the surface of the steel plate. Therefore, the viscosity of the slurry that is easy to apply is specified at 5°C.
[0069] [Method for producing magnesium oxide for annealing separator]
[0070] As a method for producing magnesium oxide, there is no particular limitation as long as magnesium oxide having the above-mentioned structure can be produced. As a method for producing magnesium oxide, for example, there can be mentioned: a method for producing magnesium oxide by reacting a magnesium raw material with an alkali raw material to synthesize magnesium hydroxide, and calcining the magnesium hydroxide. As a magnesium raw material, for example, there can be mentioned: a water-soluble magnesium salt or a hydrate thereof. As a magnesium raw material, magnesium chloride hexahydrate, magnesium chloride dihydrate, and magnesium chloride anhydrate are preferred. In addition, as a magnesium raw material, seawater, irrigation water, and bittern (brine) can also be used. It should be noted that when calcining magnesium hydroxide, as its calcination atmosphere, for example, there can be mentioned: air, nitrogen. As an alkali raw material, there can be mentioned: calcium hydroxide, sodium hydroxide, and potassium hydroxide.
[0071] As another example of a production method, there is a method of using magnesium oxide obtained by calcining the mineral magnesite. The production method is a production method in which magnesium oxide obtained from the mineral magnesite is hydrated to obtain magnesium hydroxide, and the magnesium hydroxide is calcined to obtain magnesium oxide.
[0072] Here, the meanings of the terms used in this specification regarding the firing of a sample of magnesium hydroxide are as follows. "Heating time" refers to the time from room temperature to the target maximum temperature when firing a sample. "Holding temperature" refers to the target maximum temperature when firing a sample, also known as the firing temperature. "Holding time" refers to the time to maintain the holding temperature when firing a sample. "Cooling time" refers to the time from the holding temperature to the room temperature after the holding time when firing a sample. It should be noted that cooling includes slow cooling such as cooling by cooling a sample in addition to active cooling using a cooling device.
[0073] <Firing conditions>
[0074] The shape of the particles contained in magnesium oxide, such as mesh particles, plate particles and block particles, can be controlled by adjusting the final sintering conditions when magnesium oxide is obtained and the trace elements contained in the precursor supplied to the final sintering. The sintering conditions include heating time, holding temperature, holding time and cooling time.
[0075] <Plate-shaped particles>
[0076] As a condition for obtaining magnesium oxide containing plate-like particles, for example, the heating time is preferably 0.5 hours to 2.5 hours, and more preferably 1.0 hours to 2.0 hours. The holding temperature is preferably 400°C to 700°C or 1000°C to 1300°C, and more preferably 450°C to 600°C or 1050°C to 1200°C. When the holding temperature is 400°C to 700°C, it is easy to maintain the shape of magnesium hydroxide, so it is easy to obtain plate-like particles. On the other hand, when the holding temperature is 1000°C to 1300°C, the sintering of magnesium oxide is moderately carried out, so it is easy to obtain plate-like particles. The holding time is preferably 0.1 hours to 15.0 hours, and more preferably 0.2 hours to 13.0 hours. The cooling time is preferably 0.1 hours to 6.0 hours, and more preferably 0.2 hours to 5.0 hours. It should be noted that the heating time, the holding time, and the cooling time are the same in these two temperature regions of the holding temperature.
[0077] If the holding temperature is lower than the above range, magnesium hydroxide may remain. When the holding temperature is outside the above range, i.e., 700°C to 1000°C, mesh particles are easily formed, so it is difficult to form plate-like particles. If the holding temperature is higher than the above range, sintering is excessive, and agglomerates are easily formed, so it is difficult to form plate-like particles.
[0078] <Network particles>
[0079] As conditions for obtaining magnesium oxide containing mesh particles, for example, the heating time is preferably 0.5 to 2.0 hours, more preferably 1.0 to 1.5 hours. The holding temperature is preferably 700° C. to 1000° C., more preferably 750° C. to 950° C. The holding time is preferably 0.1 to 24 hours, more preferably 0.2 to 1.0 hours. The cooling time is preferably 0.1 to 1.0 hours, more preferably 0.2 to 0.8 hours.
[0080] If the heating time, holding time and cooling time are shorter than the above-mentioned scope, it is difficult to form mesh particles, and it is easy to produce uneven firing. If the holding temperature is lower than the above-mentioned scope, it is difficult to form mesh particles. On the other hand, if the heating time, holding time and cooling time are longer than the above-mentioned scope, it is easy to form plate-like particles, and it is therefore difficult to obtain mesh particles. If the holding temperature is higher than the above-mentioned scope, it is difficult to form mesh particles. And production efficiency deteriorates.
[0081] <Blocky particles>
[0082] The heating time is preferably 0.5 to 2.5 hours, more preferably 1.0 to 2.0 hours. The holding temperature is preferably 1100° C. to 1300° C., more preferably 1200° C. to 1300° C. The holding time is preferably 0.1 to 15.0 hours, more preferably 0.2 to 13.0 hours. The cooling time is preferably 0.1 to 6.0 hours, more preferably 0.2 to 5.0 hours.
[0083] If the heating time, holding time and cooling time are shorter than the above range, plate-like particles are easily formed and block-like particles are difficult to form. If the holding temperature is lower than the above range, the particle size cannot be fully increased. On the other hand, if the heating time, holding time and cooling time are longer than the above range, the particle size becomes too large. If the holding temperature is higher than the above range, the particle size becomes too large.
[0084] <Influence of trace elements during firing>
[0085] When forming mesh particles and plate-like particles, the melting point of the material to be fired changes depending on the trace elements contained in the material to be fired. Therefore, whether the desired mesh particles and / or plate-like particles are formed is confirmed by scanning electron microscopy (SEM) before use.
[0086] For example, when the holding temperature during calcination is about 700 to 900° C., the chlorine (Cl) content has the effect of lowering the melting point of the substance to be calcined, and mainly affects the formation of network particles. The Cl content contained in the magnesium oxide obtained after calcination is preferably 0.001 to 0.1 mass %.
[0087] The content of boron (B) has the effect of lowering the melting point of the substance to be fired when the holding temperature during firing is about 1200-1300°C, and mainly affects the formation of plate-like particles and block-like particles. The content of B contained in the magnesium oxide obtained after firing is preferably 0.03-0.15% by mass. When magnesium oxide having a boron content in such a numerical range is used as an annealing separator, the magnetic properties and insulation properties of the grain-oriented electrical steel sheet can be improved.
[0088] <Firing atmosphere>
[0089] The atmosphere during firing can be nitrogen or air. It is sufficient as long as the heat is evenly contacted with the material to be fired. The material to be fired can also be evenly stirred during firing. As an apparatus for performing such firing, for example, a rotary kiln can be cited.
[0090] <Control of the Ratio of Plate-Like Particles to Mesh-Like Particles>
[0091] The ratio of plate-like particles to mesh-like particles can be controlled by mixing and adjusting the final calcined magnesium oxide having different ratios of plate-like particles to mesh-like particles. It should be noted that the final calcination conditions (e.g., heating time, holding temperature, holding time, and cooling time) when obtaining magnesium oxide can also be set, and the trace elements contained in the precursor (intermediate product) supplied to the final calcination can be controlled.
[0092] <Control of the Ratio of Plate-Shaped Particles, Net-Shaped Particles, and Agglomerated Particles>
[0093] The ratio of plate-like particles, mesh particles and block-like particles can be controlled by mixing and adjusting the final calcined magnesium oxide having different ratios of plate-like particles, mesh particles and block-like particles. It should be noted that the final calcination conditions (such as heating time, holding temperature, holding time and cooling time) when obtaining magnesium oxide can also be set, and the trace elements contained in the precursor (intermediate product) supplied to the final calcination can be controlled.
[0094] <Control of trace element content in magnesium oxide>
[0095] The content of trace elements in magnesium oxide is controlled as follows. First, the content of trace elements contained in the raw materials used to manufacture magnesium oxide is measured. Then, based on the results, trace elements are added or removed from the raw materials or intermediate products so that the content of trace elements contained in magnesium oxide reaches the desired content. Examples of raw materials include: magnesium raw materials, mineral magnesite, and alkalis that react with magnesium raw materials. Examples of intermediate products include: magnesium hydroxide.
[0096] The method of adding trace elements is not particularly limited. Regarding this method, for example, a method of mixing a compound containing the trace element as a restricted object into a raw material or an intermediate product can be cited. The mixing method can be a wet method or a dry method. It should be noted that the intermediate product contains the above-mentioned precursor.
[0097] The method for removing trace elements is not particularly limited. As for this method, for example, a method of washing a raw material or an intermediate product can be cited. As a specific example of washing, water washing can be cited.
[0098] Alternatively, different compositions of intermediate products may be mixed, the excess or deficiency of trace elements may be adjusted, and then final calcination may be performed to obtain magnesium oxide having a desired content of trace elements. Alternatively, different compositions of final calcined magnesium oxide may be mixed, the excess or deficiency of trace elements may be adjusted, and then magnesium oxide having a desired content of trace elements may be obtained.
[0099] For example, as a method for adding copper (Cu) to magnesium oxide, for example, a method of mixing copper or a copper compound into an intermediate product, adjusting the excess or deficiency of copper, and then performing final calcination can be cited. Alternatively, as this method, for example, a method of adjusting the excess or deficiency of copper by mixing a plurality of magnesium oxides after final calcination can be cited. Thus, magnesium oxide having a desired copper content can be obtained. Preferably, a method of mixing a specified amount of copper or a copper compound into a slurry of an intermediate product, magnesium hydroxide, before final calcination can be cited. Thus, copper is easily and evenly dispersed in the obtained magnesium oxide. As a preferred copper compound, for example, copper oxide (CuO) can be cited.
[0100] As a method for adding boron (B) to magnesium oxide, for example, a method of mixing a boron compound into an intermediate product, adjusting the excess or deficiency of boron, and then performing a final calcination can be cited. Alternatively, as this method, for example, a method of adjusting the excess or deficiency of boron by mixing a plurality of magnesium oxides after the final calcination can be cited. In this way, magnesium oxide having a desired boron content can be obtained. As boron compounds, for example, boric acid, alkali metal borate, ammonium borate, alkali metal metaborate, and boron dioxide can be cited.
[0101] In the manufacturing process of magnesium oxide, in addition to copper (Cu), various additives known to improve coating properties and magnetic properties can be effectively added. Examples of such additives include titanium (Ti), manganese (Mn), aluminum (Al), calcium (Ca), and compounds thereof.
[0102] <Control of Magnesium Oxide Particle Size Distribution (D10, D50, D90, MV)>
[0103] The particle size distribution of magnesium oxide can be controlled by the following method.
[0104] One method is to adjust at least one of the reaction temperature, reaction rate, and stirring conditions when the magnesium raw material and the alkali raw material react to synthesize magnesium hydroxide. Another method is to pulverize the precursor before the final calcination. Another method is to control the calcination conditions of magnesium hydroxide. Another method is to re-calcine or pulverize the magnesium oxide after the final calcination.
[0105] Under the above conditions, magnesium oxide for annealing separator is produced. Since the magnesium oxide has the above-specified structure, the magnesium oxide for annealing separator can be uniformly applied to the steel sheet.
[0106] [Method for producing grain-oriented electrical steel sheet using magnesium oxide for annealing separator]
[0107] Next, a method for producing a grain-oriented electrical steel sheet using the above-mentioned magnesium oxide for annealing separator is described. The method comprises: a coating step of coating a slurry containing the above-mentioned magnesium oxide on a steel sheet after decarburization annealing; and a high temperature annealing step of annealing the steel sheet coated with magnesium oxide.
[0108] <Coating process>
[0109] The magnesium oxide is uniformly dispersed in a liquid to form a slurry containing the magnesium oxide. The liquid may be water, for example. At this time, the slurry is formed at a low temperature of 5° C. in order to prevent the magnesium oxide from hydrating.
[0110] As described above, the concentration of magnesium oxide can be, for example, 5 to 30% by mass. From the viewpoint of being easy to apply the slurry uniformly on the steel plate without agglomeration, the lower limit of the magnesium oxide concentration is preferably 7% by mass. From the viewpoint of making the slurry a viscosity that is easy to apply, the upper limit of the concentration of the annealing separator (magnesium oxide) is preferably 25% by mass.
[0111] As described above, the viscosity of the slurry at 5°C is, for example, 2.2 to 5.2 mPa·s. From the viewpoint of ensuring a sufficient coating amount, the lower limit of the viscosity of the slurry at 5°C is preferably 2.6 mPa·s. The lower limit is more preferably 3.5 mPa·s. From the viewpoint of easy coating of the slurry, the upper limit of the viscosity of the slurry at 5°C is preferably 4.6 mPa·s.
[0112] The slurry is continuously applied to the steel sheet subjected to decarburization annealing using a roll coating device or a spray device. However, in order to prevent the magnesium oxide from hydrating, the slurry is applied at a low temperature such as 5°C. At this time, since the magnesium oxide having the above-mentioned structure is used, the slurry containing magnesium oxide can be evenly applied to the steel sheet. Then, the applied slurry is dried at a temperature of, for example, about 300 to 500°C.
[0113] <High temperature annealing process>
[0114] The slurry is applied, and then the steel sheet coated with magnesium oxide is annealed. The annealing conditions include, for example, 1000-1200°C and 10-20 hours. Thus, a forsterite film is formed on the surface of the steel sheet, and then a known prescribed treatment is performed as needed to form a grain-oriented electromagnetic steel sheet using the annealing separator.
[0115] In the method for manufacturing a grain-oriented electrical steel sheet of the present invention, magnesium oxide having the above-mentioned prescribed structure and being able to be uniformly coated on a steel sheet is used. Therefore, a forsterite coating having good coating properties can be formed on the steel sheet. Thus, a grain-oriented electrical steel sheet having improved magnetic properties can be obtained.
[0116] The magnesium oxide for annealing separator and the method for producing a grain-oriented electrical steel sheet using the same according to the present invention are not limited to the above-mentioned embodiment or the examples described below, and may be appropriately combined, replaced or modified within the scope of the object and spirit of the present invention.
[0117] <Measurement method and test method>
[0118] Various measurement methods and test methods are as follows.
[0119] 1. The particle sizes of mesh particles, plate particles, and block particles, the pore sizes of the mesh particle depressions, the total ratio of mesh particles to plate particles, and the ratio of mesh particles to plate particles
[0120] The particle size of the mesh particles and plate-like particles and the pore size of the depression of the mesh particles are photographed at a magnification of 20,000 times using a scanning electron microscope (SEM), and the images obtained are used to confirm. The particle size of the block particles is photographed at a magnification of 500 times using a scanning electron microscope (SEM), and the images obtained are used to confirm. Among them, when measuring the particle size or pore size in the image, for the particles or depressions of the measured object, the diameter of the smallest circle surrounding the particles or depressions is used as the particle size or pore size. As the range of the particle size or pore size, for example, any 10 particles or depressions are selected, and the range is from the minimum value to the maximum value. As the average value of the particle size or pore size, for example, any 10 particles or depressions are selected, and the average value of the 10 particle sizes or pore sizes is used as the average value of the final particle size or pore size.
[0121] The ratio of the total weight of the mesh particles and the plate-like particles to the total weight of magnesium oxide is photographed at a magnification of 20,000 times using a scanning electron microscope (SEM), and the obtained image is used to confirm. Specifically, the ratio of the total area of the mesh particles and the plate-like particles in the image to the image area is approximated as the ratio of the total weight of the mesh particles and the plate-like particles to the total weight of magnesium oxide. The ratio of the weight of the mesh particles and the plate-like particles is photographed at a magnification of 20,000 times using a scanning electron microscope (SEM), and the obtained image is used to confirm. Specifically, the ratio of the total area of the mesh particles in the image to the total area of the plate-like particles is approximated as the ratio of the weight of the mesh particles to the plate-like particles.
[0122] 2. Particle size distribution
[0123] The particle size distribution was measured using a particle size distribution measuring device MT3300EXI I (manufactured by Microtrac Bell Co., Ltd.). First, the particle size distribution measuring device was filled with ion exchange water and the ion exchange water was circulated. Then, an appropriate amount of sample was added thereto, and after confirming that it was within the appropriate range, the sample was circulated for 1 minute and measured. The measurement time was 30 seconds.
[0124] 3. Relationship between the number of plate-like particles and the number of mesh-like particles
[0125] The relationship between the number of plate-like particles and the number of mesh-like particles is obtained by photographing with a scanning electron microscope (SEM) at a magnification of, for example, 20,000 times or more, and visually observing the obtained image. Any particle in 100 images is selected, and the number of plate-like particles and the number of mesh-like particles are counted to calculate the ratio of the number of plate-like particles to the number of mesh-like particles.
[0126] 4. BET specific surface area, pore distribution and total pore volume
[0127] About 0.5 g of sample was weighed into a sample cell, vacuum degassed as pretreatment, and heated at 105°C for 1 hour. Then, the sample cell after pretreatment was measured by a pore distribution measuring device BELSORP MAX (manufactured by Microtrac Bell Co., Ltd.) to measure the specific surface area, pore distribution, and total pore volume caused by nitrogen adsorption. The specific surface area was analyzed by the BET multipoint method. The pore distribution was analyzed by the BJH method using the desorption isotherm. The total pore volume was calculated by the 1-point method.
[0128] 5. Content of trace elements
[0129] 0.5 g of the sample was dissolved in 5 ml of a 30% HNO3 solution and then made up to 100 ml with ultrapure water. This was used as the test solution and measured using a light emission spectrometer SPS3520-DD (manufactured by Hitachi High-Technologies Corporation) by the calibration curve method.
[0130] 6. Slurry viscosity
[0131] Pour 30 ml of ion exchange water into a beaker equipped with a stirrer and adjust the temperature to 5°C. All subsequent steps are carried out at a temperature of 5°C. Weigh 3.5 g of the sample using the tray of an electronic balance and put it into the beaker. After putting it in, let it stand for 30 seconds, then stir and mix it with a stirring rod for 2 minutes to use as the test solution. Put 7 ml of the test solution into the sample of the temperature-controlled viscometer LVDV2T (manufactured by Brucker Field Co., Ltd.) for measurement. At this time, the spindle is SC4-18 (18) and the rotation speed is 200 rpm.
[0132] 7. Slurry coating test
[0133] 3.5 g of magnesium oxide was suspended in 30 ml of water at 5°C to obtain a slurry. The obtained slurry was applied to a steel plate of 150 mm in length, 80 mm in width and 0.5 mm in thickness, homogenized by a rubber roller and fired at 500°C for 20 seconds to sinter the MgO. The obtained steel plate was photographed with an optical observation image and a 3D observation image using a Oneshot 3D shape measuring instrument VR-6000 (manufactured by Keyence Corporation).
[0134] Example
[0135] The present invention will be further described below with reference to Examples and Comparative Examples, but the present invention is not limited to these Examples and Comparative Examples.
[0136] (1) About samples
[0137] [Example 1]
[0138] A 1.7 mol / L magnesium chloride aqueous solution and a 2.2 mol / L calcium hydroxide aqueous solution were mixed and reacted at 130°C for 4 hours to obtain a magnesium hydroxide slurry. Copper oxide (CuO) was added to the obtained slurry so that the copper (Cu) content in the final magnesium oxide was 0.012% by mass. Pure water was then added to the obtained slurry to adjust the content to 0.3×10 3 mol·m -3 After adding these, the slurry was filtered and washed with pure water 20 times the mass of the solid content to obtain a filter cake of magnesium hydroxide. The obtained filter cake was dried at 180° C. for 40 minutes to obtain magnesium hydroxide.
[0139] The obtained magnesium hydroxide was fired in an air atmosphere using a rotary kiln under the conditions of a heating time of 1.25 hours, a holding temperature of 900° C., a holding time of 0.25 hours, and a cooling time of 0.25 hours to obtain a fired product. The fired product was pulverized with a jet mill to obtain magnesium oxide A. The obtained magnesium oxide A was observed with a 20,000-fold SEM photograph of any 100 particles, and as a result, it was confirmed that the particles were mesh particles, but no plate-like particles were observed.
[0140] The magnesium oxide with a D50 of 3.1 μm prepared separately was rehydrated at 90°C for 4 hours, dehydrated and dried to obtain a powder of magnesium hydroxide. The obtained magnesium hydroxide powder was fired in an air atmosphere using a tunnel kiln under the conditions of a heating time of 2 hours, a holding temperature of 1100°C, a holding time of 12 hours and a cooling time of 4 hours to obtain a fired product. The fired product was crushed with a jet mill to obtain magnesium oxide B. The obtained magnesium oxide B was observed with a 20,000-fold SEM photograph of any 100 particles. As a result, no mesh particles were observed, but it was confirmed to be plate-like particles. In addition, the obtained magnesium oxide B was observed with a 500-fold SEM photograph, and the result was confirmed to be a block particle.
[0141] Magnesium oxide B and magnesium oxide A were mixed at a weight ratio of 10:90 to prepare magnesium oxide of Example 1. In magnesium oxide of Example 1, the number of plate-like particles: the number of mesh-like particles = 10:90. Therefore, the number of plate-like particles: the number of mesh-like particles is in the range of 1:99 to 20:80.
[0142] Figure 2 This is a SEM photograph showing an example of mesh-like particles and plate-like particles in magnesium oxide of Example 1. The magnification is 20,000 times. Figure 2 (a) shows an example of a typical plate-like particle 1 . Figure 2 (b) shows an example of a typical plate-like particle 2. Figure 2 As shown in (a), the mesh particle 1 has a plurality of depressions on the surface of the plate-like particle. Its planar shape is roughly hexagonal. Several mesh particles are also observed around it. On the other hand, Figure 2 As shown in (b), although some bumps and depressions are observed on the surface of plate-like particles 2, there are no obvious depressions. Its planar shape is a deformed hexagon. Some mesh particles are also observed around it.
[0143] Figure 3 This is a SEM photograph showing an example of block particles in magnesium oxide of Example 1 to which block particles are added. The magnification is 500 times. As shown in the figure, block particles 3 have multiple faces. Small particles of mesh particles and plate-like particles are attached to the surface of block particles 3.
[0144] [Example 2]
[0145] 1.6 mol / L of bitter juice and 12 mol / L of sodium hydroxide aqueous solution were mixed and reacted at 130°C for 2 hours to obtain magnesium hydroxide slurry. The obtained slurry was filtered and washed with soft water 20 times the mass of the solid content to obtain a filter cake of magnesium hydroxide. The obtained filter cake was dried at 180°C for 40 minutes to obtain magnesium hydroxide.
[0146] The obtained magnesium hydroxide was fired in an air atmosphere using a rotary kiln under the conditions of a heating time of 0.5 hour, a holding temperature of 550° C., a holding time of 1.0 hour, and a cooling time of 0.1 hour to obtain a fired product. The fired product was crushed with an impact crusher to obtain magnesium oxide C. The obtained magnesium oxide C was observed with a 20,000-fold SEM photograph of any 100 particles. As a result, no mesh particles were observed, but plate-like particles were confirmed. In addition, the obtained magnesium oxide C was observed with a 500-fold SEM photograph, and no block particles were observed.
[0147] 1.6 mol / L of bitter juice and 12 mol / L of sodium hydroxide aqueous solution were mixed and reacted at 130°C for 2 hours to obtain magnesium hydroxide slurry. The obtained slurry was filtered and washed with soft water 20 times the mass of the solid content to obtain a filter cake of magnesium hydroxide. The obtained filter cake was dried at 150°C for 40 minutes, and the obtained dried product was crushed with an impact mill to obtain magnesium hydroxide.
[0148] The obtained magnesium hydroxide was sintered in an air atmosphere using a tunnel kiln under the conditions of a heating time of 0.5 hours, a holding temperature of 850° C., a holding time of 24 hours, and a cooling time of 0.1 hours to obtain magnesium oxide D. An arbitrary 100 particles of the obtained magnesium oxide D were observed using a 20,000-fold SEM photograph, and as a result, it was confirmed that they were mesh particles, but no plate-like particles were observed.
[0149] Magnesium oxide C and magnesium oxide D were mixed at a weight ratio of 5:95 to prepare magnesium oxide of Example 2. In magnesium oxide of Example 2, the number of plate-like particles: the number of mesh-like particles = 5:95. Therefore, the number of plate-like particles: the number of mesh-like particles is in the range of 1:99 to 20:80.
[0150] [Example 3]
[0151] Magnesium oxide C and magnesium oxide D were mixed at a weight ratio of 15:85 to prepare magnesium oxide of Example 3. In magnesium oxide of Example 3, the number of plate-like particles: the number of mesh-like particles = 15:85. Therefore, the number of plate-like particles: the number of mesh-like particles is in the range of 1:99 to 20:80.
[0152] [Comparative Example 1]
[0153] First, prepare magnesium oxide with an MgO content of 92.9wt%, a SiO2 content of 2.39wt%, a CaO content of 2.36wt%, an Al2O3 content of 0.19wt%, and a Fe2O3 content of 0.55wt% in terms of oxide conversion. In a reactor equipped with an agitator, a cooler, a thermometer, and a gas suction port, the magnesium oxide is added to an aqueous solution of ammonium nitrate at a molar ratio of NH4NO3 / MgO=2 under heating at 100°C. Then, the aqueous solution is stirred to dissolve and react the magnesium oxide to generate a magnesium nitrate solution and release ammonia. The generated ammonia is put into water, recovered with water, and concentrated to 10.0mol / L as an alkali source. The generated magnesium nitrate solution is filtered and recovered, and adjusted to 3.5mol / L as a magnesium source.
[0154] The purified magnesium nitrate solution, ammonia water and water were mixed at 25° C. in a ratio of 1.46 mol of Mg(NO3)2 (417.14 ml): 2.92 mol of NH3·H2O (292.0 ml): 16.14 mol of H2O (290.86 ml). Thus, magnesium nitrate reacted with ammonia to obtain magnesium hydroxide slurry.
[0155] The obtained magnesium hydroxide slurry was heated at 130° C. for 4 hours to obtain magnesium hydroxide slurry. An appropriate amount of boric acid aqueous solution was added to the obtained magnesium hydroxide slurry, and the slurry was filtered and washed with pure water 20 times the mass of the solid content to obtain a filter cake of magnesium hydroxide.
[0156] The obtained filter cake was dried at 180°C for 40 minutes to obtain magnesium hydroxide. The obtained magnesium hydroxide was sintered in an air atmosphere using a rotary kiln under the conditions of a heating time of 1.5 hours, a holding temperature of 900°C, a holding time of 0.5 hours and a cooling time of 0.5 hours to obtain a sintered product. The obtained sintered product was crushed by a jet mill to obtain the magnesium oxide of Comparative Example 1. The magnesium oxide of Comparative Example 1 was observed using a 20,000-fold SEM photograph of any 100 particles. As a result, the number of plate-like particles: the number of mesh-like particles = 0:100. Therefore, the number of plate-like particles:
[0157] The number of mesh particles is outside the range of 1:99 to 20:80.
[0158] Figure 4 This is a SEM photograph showing an example of particles in magnesium oxide of Comparative Example 1. The magnification is 20,000 times. As shown in the figure, the shape of the particles is such that the skeleton part is bent or deformed in any direction. Figure 2 In the case of (a), the relatively small mesh particles (or their aggregates) are present, but there are almost no plate-like particles. Although not shown, no bulk particles are observed in the SEM photograph at a magnification of 500 times.
[0159] [Comparative Example 2]
[0160] A 1.7 mol / L magnesium chloride aqueous solution and a 12 mol / L sodium hydroxide aqueous solution were mixed and reacted at 130°C for 4 hours to obtain a magnesium hydroxide slurry. The obtained slurry was filtered and washed with pure water 20 times the mass of the solid content to obtain a filter cake of magnesium hydroxide. The obtained filter cake was dried at 180°C for 40 minutes to obtain magnesium hydroxide.
[0161] The obtained magnesium hydroxide was fired in an air atmosphere using a rotary kiln under the conditions of a heating time of 1.5 hours, a holding temperature of 950°C, a holding time of 0.5 hours, and a cooling time of 0.5 hours to obtain a fired product. The fired product was crushed by a jet mill to obtain magnesium oxide of Comparative Example 2. The magnesium oxide of Comparative Example 2 obtained was observed at random using a 20,000-fold SEM photograph, and as a result, the number of plate-like particles: the number of mesh-like particles = 0:100. Therefore, the number of plate-like particles: the number of mesh-like particles is outside the range of 1:99 to 20:80.
[0162] [Comparative Example 3]
[0163] The magnesium oxide composed of magnesium oxide C alone was used as Comparative Example 3. In the magnesium oxide of Comparative Example 3, the number of plate-like particles: the number of mesh-like particles = 100: 0. Therefore, the number of plate-like particles: the number of mesh-like particles is outside the range of 1:99 to 20:80.
[0164] [Comparative Example 4]
[0165] Magnesium oxide C and magnesium oxide D were mixed at a weight ratio of 30:70 to prepare magnesium oxide of Comparative Example 4. In magnesium oxide of Comparative Example 4, the number of plate-like particles: the number of mesh-like particles = 30:70. Therefore, the number of plate-like particles: the number of mesh-like particles is outside the range of 1:99 to 20:80.
[0166] (2) About the evaluation items
[0167] The magnesium oxide of Example 1 and the magnesium oxides of Comparative Examples 1 and 2 were evaluated in terms of particle size, pit pore size, particle size distribution, slurry viscosity, trace element content, pore distribution, pore volume, BET specific surface area, and slurry coating test.
[0168] Regarding Example 2, Example 3, Comparative Example 3, and Comparative Example 4, the particle size, the pore size of the depression, the particle size distribution, the content of trace elements, the pore distribution, the pore volume, the BET specific surface area, and the slurry coating test were evaluated.
[0169] (3) Evaluation results
[0170] (a) Particle size and pore size of the depression
[0171] In the magnesium oxide of Example 1, Example 2 and Example 3, the particle size of the mesh particles is approximately in the range of 0.05 to 5 μm. In the magnesium oxide of Example 1, Example 2 and Example 3, the pore size of the depression of the mesh particles is approximately in the range of 0.005 to 0.2 μm. In the magnesium oxide of Example 1, Example 2 and Example 3, the particle size of the plate-like particles is approximately in the range of 0.05 to 5 μm, which is equivalent to the mesh particles. In the magnesium oxide of Example 1, the particle size of the blocky particles is approximately in the range of 5 to 100 μm.
[0172] On the other hand, in the magnesium oxide of Comparative Examples 1 and 2, mesh-like particles were formed, but plate-like particles were not formed.
[0173] (b) Particle size distribution
[0174] In the magnesium oxide of Example 1, D10=1.24 μm, D50=2.55 μm, D90=9.97 μm, and the volume mean diameter MV is 4.57 μm.
[0175] In the magnesium oxide of Example 2, D10=0.77 μm, D50=1.53 μm, D90=2.54 μm, and the volume mean diameter MV is 1.62 μm.
[0176] In the magnesium oxide of Example 3, D10=0.72 μm, D50=1.54 μm, D90=2.58 μm, and the volume mean diameter MV is 1.62 μm.
[0177] That is, in the magnesium oxide of Examples 1, 2 and 3, D10 is in the range of 0.65 to 1.7 μm, D50 is in the range of 1.5 to 3.6 μm, D90 is in the range of 2.0 to 14 μm, and MV is in the range of 1.55 to 6.4 μm. That is, the particle size distribution of the magnesium oxide of Examples 1, 2 and 3 is a relatively small particle size.
[0178] On the other hand, in the magnesium oxide of Comparative Example 1, D10=1.29 μm, D50=6.15 μm, D90=40.01 μm, and the volume mean diameter MV is 17.17 μm. That is, the magnesium oxide of Comparative Example 1 has a D10 within the range of 0.65 to 1.7 μm, a D50 outside the range of 1.5 to 3.6 μm, a D90 outside the range of 2.0 to 14 μm, and a MV outside the range of 1.55 to 6.4 μm.
[0179] In the magnesium oxide of Comparative Example 2, D10=1.02 μm, D50=3.86 μm, D90=70.52 μm, and the volume mean diameter MV is 25.53 μm. That is, the magnesium oxide of Comparative Example 2 has a D10 within the range of 0.65 to 1.7 μm, a D50 outside the range of 1.5 to 3.6 μm, a D90 outside the range of 2.0 to 14 μm, and a MV outside the range of 1.55 to 6.4 μm.
[0180] In the magnesium oxide of Comparative Example 3, D10=1.14 μm, D50=4.00 μm, D90=6.75 μm, and the volume mean diameter MV is 4.12 μm. That is, the magnesium oxide of Comparative Example 3 has a D10 in the range of 0.65 to 1.7 μm, a D50 in the range of 1.5 to 3.6 μm, a D90 in the range of 2.0 to 14 μm, and a MV in the range of 1.55 to 6.4 μm.
[0181] That is, the particle size distribution of the magnesium oxide in Comparative Examples 1, 2, and 3 is a relatively large particle size.
[0182] In the magnesium oxide of Comparative Example 4, D10=0.52 μm, D50=1.43 μm, D90=2.57 μm, and the volume mean diameter MV is 1.50 μm. That is, the magnesium oxide of Comparative Example 4 has a D10 outside the range of 0.65 to 1.7 μm, a D50 outside the range of 1.5 to 3.6 μm, a D90 within the range of 2.0 to 14 μm, and a MV outside the range of 1.55 to 6.4 μm.
[0183] That is, the particle size distribution of the magnesium oxide in Comparative Example 4 is a relatively small particle size.
[0184] (c) Slurry viscosity
[0185] In the magnesium oxide of Example 1, the viscosity of the slurry at 5° C. was 3.69 mPa·s. Therefore, the viscosity of the slurry at 5° C. was within the range of 2.2 to 5.2 mPa·s, which is easy to apply.
[0186] On the other hand, the viscosity of the slurry at 5° C. was 3.39 mPa·s and 3.70 mPa·s, respectively, in the magnesium oxide of Comparative Examples 1 and 2. Therefore, the viscosity of the slurry at 5° C. was within the range of 2.2 to 5.2 mPa·s, which is easy to apply.
[0187] (d) Content of trace elements
[0188] In the magnesium oxide of Example 1, as representative trace elements, boron (B) is 795 ppm, aluminum (Al) is 205 ppm, copper (Cu) is 109 ppm, iron (Fe) is 266 ppm, manganese (Mn) is 91 ppm, and titanium (Ti) is 12 ppm.
[0189] In the magnesium oxide of Example 2, as representative trace elements, boron (B) is 236 ppm, aluminum (Al) is 51 ppm, copper (Cu) is 4 ppm, iron (Fe) is 2 ppm, manganese (Mn) is less than 1 ppm, and titanium (Ti) is less than 1 ppm.
[0190] In the magnesium oxide of Example 3, as representative trace elements, boron (B) is 244 ppm, aluminum (Al) is 261 ppm, copper (Cu) is 4 ppm, iron (Fe) is 8 ppm, manganese (Mn) is less than 1 ppm, and titanium (Ti) is less than 1 ppm.
[0191] On the other hand, in the magnesium oxide of Comparative Example 1, as representative trace elements, boron (B) is 852 ppm, aluminum (Al) is 22 ppm, copper (Cu) is 1 ppm, iron (Fe) is 135 ppm, manganese (Mn) is 8 ppm, and titanium (Ti) is 2 ppm.
[0192] In the magnesium oxide of Comparative Example 2, as representative trace elements, boron (B) is 200 ppm, aluminum (Al) is less than 1 ppm, copper (Cu) is 2 ppm, iron (Fe) is 0 ppm, manganese (Mn) is less than 1 ppm, and titanium (Ti) is less than 1 ppm.
[0193] In the magnesium oxide of Comparative Example 3, as representative trace elements, boron (B) is 144 ppm, aluminum (Al) is 22 ppm, copper (Cu) is 4 ppm, iron (Fe) is less than 1 ppm, manganese (Mn) is less than 1 ppm, and titanium (Ti) is less than 1 ppm.
[0194] In the magnesium oxide of Comparative Example 4, as representative trace elements, boron (B) is 240 ppm, aluminum (Al) is 331 ppm, copper (Cu) is 4 ppm, iron (Fe) is 11 ppm, manganese (Mn) is less than 1 ppm, and titanium (Ti) is less than 1 ppm.
[0195] The results of (b) to (d) above are summarized in Table 1.
[0196] [Table 1]
[0197]
[0198] (e) Pore distribution, pore volume and BET specific surface area
[0199] Figure 5 This is a graph showing an example of pore distribution in magnesium oxide of Example 1. The vertical axis is the differential pore volume (cm 3 ·g -1 ·nm -1 ), the horizontal axis is the pore diameter (nm). In the magnesium oxide of Example 1, the total pore volume is 0.276 cm 3 / g, BET specific surface area is 16.84m 2 / g. Therefore, the total pore volume and BET specific surface area are relatively large. In addition, there are peaks of pore volume near pore diameters of 2 to 6 nm and near pore diameters of 20 to 70 nm.
[0200] Figure 6 This is a graph showing an example of pore distribution in magnesium oxide of Example 2. The vertical axis is the differential pore volume (cm 3 ·g -1 ·nm -1 ), the horizontal axis is the pore diameter (nm). In the magnesium oxide of Example 2, the total pore volume is 0.290 cm 3 / g, BET specific surface area is 20.28m 2 / g. Therefore, the total pore volume and BET specific surface area are relatively large. In addition, there are peaks of pore volume near pore diameters of 2 to 6 nm and near pore diameters of 30 to 70 nm.
[0201] Figure 7 This is a graph showing an example of pore distribution in magnesium oxide of Example 3. The vertical axis is the differential pore volume (cm 3 ·g -1 ·nm-1 ), the horizontal axis is the pore diameter (nm). In the magnesium oxide of Example 3, the total pore volume is 0.259 cm 3 / g, BET specific surface area is 32.83m 2 / g. Therefore, the total pore volume and BET specific surface area are relatively small. In addition, there is a peak of pore volume near pore diameter 3 to 6 nm. There is a peak of pore volume near pore diameter 30 to 70 nm, but it is small.
[0202] Figure 8 This is a graph showing an example of pore distribution in magnesium oxide of Comparative Example 1. The vertical axis is the differential pore volume (cm 3 ·g -1 ·nm -1 ), the horizontal axis is the pore diameter (nm). In the magnesium oxide of Comparative Example 1, the total pore volume is 0.201 cm 3 / g, BET specific surface area is 15.34m 2 / g. Therefore, the total pore volume and BET specific surface area are relatively small. In addition, there is a peak of pore volume near pore diameter 2-6nm. However, there is no peak of pore volume near pore diameter 20-70nm. There is a peak of pore volume near pore diameter 50-80nm, but it is small.
[0203] Fig. 9 This is a graph showing an example of pore distribution in magnesium oxide of Comparative Example 3. The vertical axis is the differential pore volume (cm 3 ·g -1 ·nm -1 ), the horizontal axis is the pore diameter (nm). In the magnesium oxide of Comparative Example 3, the total pore volume is 0.281 cm 3 / g, BET specific surface area is 121.67m 2 / g. Therefore, the total pore volume and BET specific surface area are relatively small. In addition, there is a peak in the pore volume near the pore diameter of 3 to 6 nm.
[0204] Fig.10 This is a graph showing an example of pore distribution in magnesium oxide of Comparative Example 4. The vertical axis is the differential pore volume (cm 3 ·g -1 ·nm -1 ), the horizontal axis is the pore diameter (nm). In the magnesium oxide of Comparative Example 4, the total pore volume is 0.282 cm 3 / g, BET specific surface area is 46.43m 2 / g. Therefore, the total pore volume and BET specific surface area are relatively small. In addition, there is a peak in the pore volume near the pore diameter of 3 to 6 nm.
[0205] (f) Optical observation image and 3D observation image based on coating test
[0206] Fig.11 This is an optical observation image showing an example of the coating test result of magnesium oxide in Example 1. The magnification is 40 times. Fig.12 This is a 3D observation image showing an example of the coating test result of magnesium oxide in Example 1. The magnification is 120 times. As shown in the figure, in the coating film formed from the slurry containing magnesium oxide in Example 1, it is found that there are few spots and lumps.
[0207] Fig.13 This is a 3D observation image showing an example of the coating test result of magnesium oxide in Example 2. The magnification is 120 times. As shown in the figure, in the coating film formed from the slurry containing magnesium oxide in Example 2, it is found that there are few spots and lumps.
[0208] Fig.14 This is a 3D observation image showing an example of the coating test result of magnesium oxide in Example 3. The magnification is 120 times. As shown in the figure, in the coating film formed from the slurry containing magnesium oxide in Example 3, it is found that there are few spots and lumps.
[0209] on the other hand, Fig.15 This is an optical observation image showing an example of the coating test result of magnesium oxide in Comparative Example 1. The magnification is 40 times. Fig.16 This is a 3D observation image showing an example of the coating test result of magnesium oxide of Comparative Example 1. The magnification is 120 times. As shown in the figure, in the coating film formed from the slurry containing magnesium oxide of Comparative Example 1, it is found that there are many spots and lumps.
[0210] Fig.17 This is a 3D observation image showing an example of the coating test result of magnesium oxide of Comparative Example 3. The magnification is 120 times. As shown in the figure, in the coating film formed from the slurry containing magnesium oxide of Comparative Example 3, it is found that there are many spots and lumps.
[0211] Fig.18 This is a 3D observation image showing an example of the coating test result of magnesium oxide of Comparative Example 4. The magnification is 120 times. As shown in the figure, in the coating film formed from the slurry containing magnesium oxide of Comparative Example 4, it is found that there are many spots and lumps.
[0212] From the above data, it can be seen that the magnesium oxide for annealing separator of the present invention has the above-mentioned specified composition, so the magnesium oxide for annealing separator can be evenly coated on the steel sheet. Therefore, by using the magnesium oxide for annealing separator, a forsterite coating with good coating properties can be obtained. Therefore, the magnetic properties of the grain-oriented electrical steel sheet manufactured using the magnesium oxide for annealing separator can be improved.
[0213] Description of Reference Numerals
[0214] 1 mesh particles
[0215] 2 plate-like particles
[0216] 3 Blocky particles
[0217] 11 Surface
[0218] 12 Depression
[0219] 21 Surface
Claims
1. Magnesium oxide for annealing separator, wherein: The magnesium oxide comprises: A mesh particle having multiple depressions on the surface, and plate-like particles, The ratio of the number of the plate-like particles to the number of the mesh-like particles is 1:99 to 20:80, The particle size of the mesh particles is 0.05 to 5 μm. The size of each of the plurality of depressions is 0.005 to 0.2 μm, The plate-like particles have a particle size of 0.05 to 5 μm.
2. The magnesium oxide for annealing separator according to claim 1, wherein The magnesium oxide contains copper, The copper content is 3-200 ppm.
3. The magnesium oxide for annealing separator according to claim 1, wherein In the particle size distribution of the magnesium oxide, D10 is 0.65~1.7μm, D50 is 1.5~3.6μm, D90 is 2.0~14μm, The volume average diameter is 1.55 to 6.4 μm.
4. The magnesium oxide for annealing separator according to claim 1, wherein The magnesium oxide further includes block-like particles larger than the plate-like particles and the mesh-like particles.
5. The magnesium oxide for annealing separator according to claim 1, wherein When a slurry containing 5 to 30% by mass of the magnesium oxide is formed using water as a solvent, the viscosity of the slurry at 5° C. is 2.2 to 5.2 mPa·s.
6. A method for manufacturing a grain-oriented electromagnetic steel sheet, comprising the following steps: a coating step of coating a slurry containing magnesium oxide for annealing separator according to claim 1 on the steel sheet after decarburization annealing, and The high temperature annealing step anneals the steel sheet coated with the slurry.
Citation Information
Patent Citations
Separating agent for annealing for grain-oriented silicon steel sheet
JP1992056781A
Magnesium oxide for annealing separators, and grain-oriented magnetic steel sheet
CN108884509A
Preparation method of annealing separant, annealing separant and grain-oriented electromagnetic steel plate
CN113388725A